Interdisciplinary Collaboration Management at Vocational Education - Pujiastuti, Rr. Sri Endang; Ardiyanto, Jefri; Mukti, Gatot Ari; Susanto, Edy; Asri, Asri; Widiyati, Sri (Proceedings of International Conference on Science, Education, and Technology, 2024)
Interdisciplinary Collaboration Management in vocational education is an approach that encourages interdisciplinary collaboration in the development and implementation of vocational education programs. This approach aims to produce graduates who have more holistic competencies and are ready to face the complexity of the dynamic world of work. The development of interdisciplinary collaboration management can be developed through curriculum design that integrates knowledge and skills from various fields. This type of research uses a literature review with a narrative review design, namely looking for articles related to interprofessional collaboration that have been published in journals. Journals were selected based on predetermined criteria. Collaborative faculty from different disciplines can work together to provide instruction that is more comprehensive and relevant to the needs of society. This is also true in the health sector. Health vocational education curricula can be designed to integrate knowledge and skills from various disciplines, such as medicine, nursing, physiotherapy, pharmacy and nutrition. This will result in graduates who have a more thorough understanding of the health system and can work effectively with other health professionals. The development of interdisciplinary collaborative management can also improve the quality of education by integrating theory and practice. Thus, students can be better prepared for the rapid changes in the world of work and have better skills to collaborate with peers. Therefore, this approach is crucial in improving the quality of vocational education and being ready for the complexity of the dynamic world of work.